2006
DOI: 10.2170/physiolsci.rp001905
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Composition and Role of Na+,K+-ATPases in Ventricular Myocytes

Abstract: Na + ,K + -ATPases are composed of one α and one β subunit; four α and three β isoforms have been found to date. We elucidated which α and β subunits were present in the ventricular myocytes of rat and guinea-pig and what roles the Na + ,K + -ATPase isozymes play in cardiac contraction. The presence of the α1, α2, and α3 subunits and the β1 and β2 subunits in rat and guinea-pig hearts were confirmed at the protein or mRNA level. Immunocytochemistry showed a patchy presence of α1 in the transverse tubules and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…(a) Na + , K + -ATPase evaluated based on the expression of the β 1 isoform was detected in both the basolateral and apical domains, consistent with the findings of Hu et al ( 1994 ). (b) The predominant combination at the apical membrane domain of polarized ARPE-19 cells is the α 2 β 2 combination, which is consistent with the concept that the α 2 isoform is the preferred binding partner of the β 2 isoform in assembling the Na + , K + -ATPase in different tissues (Lin et al, 2005 ; Harada et al, 2006 ; Tokhtaeva et al, 2012 ) and with the co-localization of α 2 β 2 in human eye sections shown in this work. (c) Polarized ARPE-19 monolayers express Na + , K + -ATPase subunits in a membrane domain-specific pattern: α 1 is detected only at the basolateral domain, α 2 is present only in the apical domain (as seen in Figure 6 ), β 1 subunits are localized in both the basolateral and apical domains, β 2 subunits are preferentially localized in the apical domain, and β 3 subunits are exclusively localized in the basolateral domain.…”
Section: Discussionsupporting
confidence: 81%
“…(a) Na + , K + -ATPase evaluated based on the expression of the β 1 isoform was detected in both the basolateral and apical domains, consistent with the findings of Hu et al ( 1994 ). (b) The predominant combination at the apical membrane domain of polarized ARPE-19 cells is the α 2 β 2 combination, which is consistent with the concept that the α 2 isoform is the preferred binding partner of the β 2 isoform in assembling the Na + , K + -ATPase in different tissues (Lin et al, 2005 ; Harada et al, 2006 ; Tokhtaeva et al, 2012 ) and with the co-localization of α 2 β 2 in human eye sections shown in this work. (c) Polarized ARPE-19 monolayers express Na + , K + -ATPase subunits in a membrane domain-specific pattern: α 1 is detected only at the basolateral domain, α 2 is present only in the apical domain (as seen in Figure 6 ), β 1 subunits are localized in both the basolateral and apical domains, β 2 subunits are preferentially localized in the apical domain, and β 3 subunits are exclusively localized in the basolateral domain.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the preferential formation of the ␣ 2 -␤ 2 complexes in the brain is determined not only by cell-specific co-expression of these isoforms, but also by their binding preferences. Preferential formation of the ␣ 2 -␤ 2 was also detected in heart and adrenal medullary cells, where the ␣ 1 subunit is more abundant than the ␣ 2 subunit (26,27), emphasizing preferential ␤ 2 subunit binding to the ␣ 2 subunit.…”
Section: Discussionmentioning
confidence: 88%
“…These data imply that in cells co-expressing multiple Na,K-ATPase subunits isoforms, various ␣ and ␤ isoforms also assemble in different combinations, dependent on their relative cellular content. However, selective co-immunoprecipitation of the ␣ 2 subunit but not of the ubiquitously expressed ␣ 1 subunit, with the ␤ 2 subunit from mouse and rat brain (19,26), as well as from heart and adrenal medullary cells of guinea pigs and rats (26,27) suggest that the ␣ 2 subunit is the preferred binding partner of the ␤ 2 subunit. In support of this hypothesis, the tissue expres-sion pattern of the ␤ 2 subunit, mainly in muscle and nervous system, is similar to that of the ␣ 2 subunit (3,7).…”
mentioning
confidence: 94%
“…Whereas staining for agrin was relatively uniform and similar to that seen in embryonic myocytes, ␣3 Na,K-ATPase appeared as intensely labeled foci distributed within a lower, evenly labeled background. Previous studies have also reported low levels of ␣3 subunit expression in adult rodent heart (23,27,28).…”
Section: Agrin Binds Specifically To the ␣3 Nak-atpase In Heart-mentioning
confidence: 85%